Effects of a 10-day high-intensity interval training mesocycle on physical performance in male judo athletes - Jokinen, Jaana (2020)
Judo is an Olympic combat sport where the competition emphasizes several consecutive 20-30 seconds high-intensity efforts interspersed by short recovery periods. High-intensity block training has been found to be an efficient way to develop physical performance, wherein shorter training periods are focused on developing one or two chosen physical abilities. The purpose of this study was to investigate the effects of a 10-day high-intensity interval training period on the performance in male judo athletes. The study included pre and post-tests as well as a 10-day training intervention. The subjects were 19-28 years old men who had competed at least at the Nordic level during the last year (n = 7). The training period included simulated judo matches (4x4 min or intermittent 20–120 s work periods, 85–90%/HRmax) as interval training. In addition, there were technique and tactical training sessions at lighter intensity (50–60% of maximum). Moreover, in strength exercises, maximum strength was maintained sustainably with 2–4 repetitions (90–95% 1 RM). The study included measurements of the neuromuscular system for countermovement jump (CMJ), squat jump (SJ) and power in bench press (BP) and squat, maximum isometric strength (BP and leg press), as well as measurements of maximal anaerobic and aerobic performance (30 s Wingate and incremental VO2max running test). Furthermore, the control measurements were taken during the first and last HIIT session of the training period. The variables measured were the CMJ and the power output in the bench press. There were no statistically significant changes in the neuromuscular system. However, muscle power improved slightly in SJ (2.4%), squat (2.5%) and BP (3.1%) from pre to post. Maximum isometric strength levels remained almost the same. The change in leg press was -2.3% and in BP 1.0%. A significant correlation was found between relative maximum BP and its relative change (r = 0.761, p = 0.047). The relative mean power change in the anaerobic Wingate was -1.2%. Blood lactate 4 min after the Wingate decreased significantly (-11.8%, p = 0.03). Significant correlations were found between the relative and absolute VO2max pre and their pre-post changes (r = -0.831, p = 0.02 and r = -0.775, p = 0.04). Acute responses showed no significant changes for CMJ (from -1.5% to 2.3%) nor for BP (from -4.4% to -0.9%) within a single HIIT session. The 10-day short-term HIIT mesocycle implemented as simulated judo matches might not improve the physical performance characteristics in male judo athletes. At least more time for the recovery and tapering should be needed after the HIIT block before the competition.